How Does Culture Shape Creativity? A Mini-Review - Shao, Yong; Zhang, Chenchen; Zhou, Jing; Gu, Ting; Yuan, Yuan (Frontiers in Psychology, 2019)
The purpose of this study was to examine how culture shapes creativity by reviewing empirical findings across diverse studies. The impact of culture on creativity is typically manifested in three ways: (a) people from different cultures or settings have distinct implicit and/or explicit conceptions of creativity; (b) individuals from different cultures, particularly those from individualist and collectivist cultures, show differences in preferred creative processes and creative processing modes (e.g., usefulness seems more important than novelty in the East, whereas novelty seems equally important as usefulness, if not more so, in the West) when they are engaged in creative endeavors; (c) creativity may be assessed using different measures based on culture-related contents or materials, and findings are accurate only when culturally appropriate or culturally fair measures are used. Potential implications and future directions are also proposed.